« Smara, ville de nos illusions ». Les carnets de route de Michel Vieuchange en tant qu’autobiogéographie - Sokołowicz, Małgorzata (Studia Romanica Posnaniensia, 2023)
The present paper focuses on the travel notes by Michel Vieuchange (1904-1930), a young Frenchman who decided to reach Smara, a holy Muslim city located in the middle of the desert, to describe it, and to e term used by Michel Collot means telling your life through the places that has affected you. In the case of Vieuchange’s notes the geographical descriptions intervene with the description of the personality of the traveler and form a whole. The paper shows that three cities, Tiznit, Tigilit and Smara, mark three stages of the travel and correspond to different aspects of Vieuchange’s personality.